Implementation of Inclusive Education Policy for ABK in Subang Regency - Adistyana Pitaloka Kusmawati; Arita Marini; Nafiah Marathon (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
This study aims to be able to implement inclusive education policies for Children with Special Needs in Subang Regency, West Java. Children with special needs are someone who has special physical limitations, such as visually impaired, mentally retarded, ADHD, and others. In Indonesia, children with special needs can continue their education to Extraordinary Schools (SLB) where these schools have skilled teachers and are able to provide motivation to learn for students with special needs. The research method used in this research is qualitative with a descriptive approach. This study describes the policies relating to children with special needs. The data collection techniques required are several policy documents regarding children with special needs in Subang district. After document analysis, the data analysis technique used is the content analysis approach. The results of this study indicate that the implementation of inclusive education policies in Subang, school as an environment that plays a major role in changes in ABK students requires support from all parties. The role of parents, special schools, experts, universities, special schools, and the government is still considered minimal. School facilities such as facilities and infrastructure are also still limited.